1988
DOI: 10.1007/bf01655502
|View full text |Cite
|
Sign up to set email alerts
|

Increased incidence of pancreatic neoplasia in pernicious anemia

Abstract: In a Swedish population, 361 patients with pernicious anemia were followed closely during a 7‐year period with regard to the occurrence of all forms of malignant neoplasia. In addition to an increased incidence of gastric neoplasia (0.6%/year), there seemed to be an increased incidence of pancreatic neoplasia (0.3%/year) in the series. With reference to age‐ and sex‐specific incidence rates in the general population, the number of malignant pancreatic tumors observed was significantly higher than expected (p<0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
1
2

Year Published

1990
1990
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 29 publications
0
18
1
2
Order By: Relevance
“…54 Another Swedish study followed 361 patients with pernicious anaemia for 7 years and reported a 0.6% annual incidence of gastric cancer. 55 Other studies also reported that the gastric cancer risk in patients with pernicious anaemia was three-to five-fold increased. [56][57][58][59][60][61][62] Several prospective studies focused on the development of gastric cancer in patients with intestinal metaplasia type III or more severe dysplasia.…”
Section: Atrophy Metaplasia and Gastric Cancer: Prospective Studiesmentioning
confidence: 99%
“…54 Another Swedish study followed 361 patients with pernicious anaemia for 7 years and reported a 0.6% annual incidence of gastric cancer. 55 Other studies also reported that the gastric cancer risk in patients with pernicious anaemia was three-to five-fold increased. [56][57][58][59][60][61][62] Several prospective studies focused on the development of gastric cancer in patients with intestinal metaplasia type III or more severe dysplasia.…”
Section: Atrophy Metaplasia and Gastric Cancer: Prospective Studiesmentioning
confidence: 99%
“…About 30% of cases are attributable to smoking. 1,4 An increased frequency of pancreatic cancer has been suggested among individuals with a long-standing history of diabetes, 5,6 chronic pancreatitis, 7,8 pernicious anemia 9 and inheritable syndromes such as familial adenomatous polyposis. 10,11 An elevated risk of pancreatic cancer has also been seen in families with a history of breast cancer and BRCA2 mutations.…”
mentioning
confidence: 99%
“…Several previous studies have documented an increased incidence of stomach cancer in patients with pernicious anaemia (PA) (Blackburn et al, 1968;Elsborg and Mosbech, 1979;Borch et al, 1988;Brinton et al, 1989;Hsing et al, 1993). An increase in the risk for other upper gastrointestinal cancers such as buccal cavity and pharynx (Brinton et al, 1989;Hsing et al, 1993) and oesophagus (Hsing et al, 1993) has also been reported, as well as increases for other digestive organ cancers [liver, biliary tract and pancreas (Hsing et al, 1993)], though these cancers have been investigated less extensively among PA patients than stomach cancer.…”
mentioning
confidence: 99%